The Four Nobel Truths of Vedana (Bodhi Path, 2024)
The core belief of Buddhism is represented by the Four Noble Truths. It serves as the cornerstone of the middle path. And while there is happiness in the world, of course, both are momentary because there is suffering or unhappiness in it. The four noble truths, which the Buddha taught, are significant in this regard. The four noble truths also show that the cycle of consciousness and suffering are impermanent. The first and second noble truths admonish us to consider carefully on ecological principles. The first noble truth states that the suffering that results from traditional lifestyles is permanent.According to the second noble truth, ignorance-based desire that's what causes suffering. The second noble truth, which emphasises desire as the source of experiencing pain, serves as the cornerstone of a Buddhist environmental ethic. The third noble truth asserts that efforts can now be made to lessen or completely eradicate environmental issues. Because of their ignorance of nature, people must realise that they are a part of the natural world, just like all other living things. The fourth noble truth declares that it is our duty to come to an agreement on the fundamental duties to end suffering in the world.The noble eightfold path includes cultivating a deep compassion for all other living things trapped in this web of dependent originations. This compassion or empathy is necessary for the Buddhist road to freedom. The idea of dependent origination has several implications, one of which is that there is no anthropocentric bias favouring people over the natural world. Interestingly, the non-self-teaching takes on ontology in Buddhism and ultimately leads to the conclusion among Buddhists that there is a common boundary between cycle of rebirth and in another. All living things that are troubled and afflicted are the targets of compassion. On the emotional side, it stands for love, goodness, tolerance, and other great values
Keywords: FOUR NOBEL TRUTHS; VEDANA; noble eightfold path